Autophagy Induced by Palmitic Acid Regulates Neutrophil Adhesion Through the Granule-Dependent Degradation of αMβ2 Integrin in Dairy Cows With Fatty Liver - Peng, Zhicheng; Zhao, Chenxu; Du, Xiliang; Yang, Yuchen; Li, Yunfei; Song, Yuxiang; Fang, Baochen; Zhang, Yuming; Qin, Xia; Zhang, Yuanyuan; Li, Xiaobing; Wang, Zhe; et al. (Frontiers in Immunology, 2021)
β2 Integrins are critical for neutrophil firm adhesion, trans-endothelial migration and the recruitment to inflamed tissue. Autophagy is implicated in cell migration and tumor metastasis through facilitating the turnover of the β1 integrins, whether autophagy enable control neutrophil migration by promoting the degradation of β2 integrins is unexplored. Here, we confirmed that high blood levels of palmitic acid (PA) strongly triggered neutrophil autophagy overactivity and adhesion deficiency in dairy cows with fatty liver. The three neutrophil granule subtypes, namely, azurophil granules (AGs), specific granules (SGs) and gelatinase granules (GGs) were engulfed by the autophagosomes for degradation, resulting in an increased vacuolation in fatty liver dairy cow neutrophils. Importantly, the adhesion-associated molecules CD11b and CD18 distributed on AGs，SGs，GGs were degraded with the three granule subtypes by autophagy. Moreover, FGA, Hsc70 and TRIM21 mediated the degradation of cytosolic oxidized ubiquitinated CD11b and CD18. Collectively, our results demonstrate that high blood PA triggers neutrophil autophagy-dependent vacuolation and granule-dependent adhesion deficiency, thereby further decreasing neutrophil mobility, and eventually impairing the innate immune system of dairy cow with fatty liver. This theory extents the category of autophagy in maintaining granule homeostasis and provides a novel strategy to improve the immune of dairy cows with metabolic disease.